The role of taxation measures in the management of harmful products, services, and practices in Iran: a qualitative study - Mahdi Kooshkebaghi; Hossein Dargahi; Sara Emamgholipour (BMC, 2022)
Abstract Background and aim Levying a tax on harmful products, services, and practices can affect consumer choices, effectively preventing diseases and reducing health care costs. The goal of this study was to investigate the role of taxation as a powerful financial tool in the management of harmful products, services, and practices to maintain and improve public health and preserve the financial sustainability of the health care system. Materials and methods This qualitative study was conducted in 2020-2021. In order to collect information for this study, semi-structured interviews were conducted. Using purposive and snowball sampling methods, 38 managers, policymakers, economists, and key experts were interviewed. Data were analyzed using the content analysis method. The transcribed interviews were further imported into MAXQDA for classification, and relevant codes were extracted. Findings In this study, 6 main themes and 19 subthemes were labeled. The main themes included 1) objectives, effects, and requirements of the taxation of harmful products, services, and practices, 2) definition, instances, elasticity, and grading of harmful products, services, and practices, 3) Problems in controlling harmful products, services, and practices, 4) controlling harmful products, services, and practices, 5) traffic violations and accidents, and social harms, and 6) tax revenue use and the share of health care. The effects of taxing harmful products include reduced access to these products, reduced demand for harmful products, and the promotion of public health. Conclusion Harmful products, services, and practices have major health and financial implications for individuals, families, and society. To improve public health, the demand for these products and services can be controlled through taxation measures to push consumers toward less harmful alternatives.